2024
DOI: 10.3390/su16104066
|View full text |Cite
|
Sign up to set email alerts
|

Combined Toxicity of Polystyrene Nanoplastics and Pyriproxyfen to Daphnia magna

Hua-Bing Jia,
Yu-Hang Zhang,
Rong-Yao Gao
et al.

Abstract: In recent years, the adverse effects of nanoplastics (NPs) and pyriproxyfen on aquatic environments have attracted widespread attention. However, research on their combined exposure to aquatic organisms could be more extensive. This work evaluated the acute and chronic toxic effects of polystyrene NPs (PS-NPs) and pyriproxyfen on Daphnia magna (D. magna) under their combined exposure conditions. The addition of PS-NPs within 24 h reduced the acute toxicity of pyriproxyfen to D. magna, resulting in an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Studies found that the reproduction of Daphnia magna was diminished by 100% at high concentrations of pharmaceutical pollutants [41]. The rate of survival and fecundity of Daphnia magna critically reduce in 0.33 mg/l concentration of chlorpromazine and 0.128 mg/l concentration of propranolol [51]. When ibuprofen is released into the environment, it aids the growth of fungus, which significantly enhances toxicity [52].…”
Section: Animalsmentioning
confidence: 99%
“…Studies found that the reproduction of Daphnia magna was diminished by 100% at high concentrations of pharmaceutical pollutants [41]. The rate of survival and fecundity of Daphnia magna critically reduce in 0.33 mg/l concentration of chlorpromazine and 0.128 mg/l concentration of propranolol [51]. When ibuprofen is released into the environment, it aids the growth of fungus, which significantly enhances toxicity [52].…”
Section: Animalsmentioning
confidence: 99%